Brain Waste? Educated Immigrants in the U.S. Labor Market - Mattoo, Aaditya; Neagu, Ileana Cristina; Özden, Çağlar (World Bank, Washington, DC, 2012)
The authors investigate the occupational placement of immigrants in the U.S. labor market using census data. They find striking differences among highly educated immigrants from different countries, even after they control for individuals' age, experience, and level of education. With some exceptions, educated immigrants from Latin American and Eastern European countries are more likely to end up in unskilled jobs than immigrants from Asia and industrial countries. A large part of the variation can be explained by attributes of the country of origin that influence the quality of human capital, such as expenditure on tertiary education and the use of English as a medium of instruction. Performance is adversely affected by military conflict at home which may weaken institutions that create human capital and lower the threshold quality of immigrants. The selection effects of U.S. immigration policy also play an important role in explaining cross-country variation. The observed under-placement of educated migrants might be alleviated if home and host countries cooperate by sharing information on labor market conditions and work toward the recognition of qualifications.